2021
DOI: 10.1002/app.50552
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and antibacterial activity of chitosan/silicone rubber filled zeolite, silver, and copper nanocomposites againstPseudomonas aeruginosaand methicillin‐resistantStaphylococcus aureus

Abstract: The ongoing emergence of antibiotic‐resistant bacteria has become one of the biggest threats to global health and development today. Pseudomonas aeruginosa and methicillin‐resistant Staphylococcus aureus (MRSA) are important antibiotic‐resistant bacteria due to their increasing resistance to a broad array of antimicrobial agents. Herein, we developed a novel antibacterial nanocomposite based on chitosan and liquid silicone rubber filled zeolite‐A, Ag, and Cu nanoparticles with remarkable antibacterial activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Nanocomposite films consisting of CS, and AgNPs, CuO NPs or TiO 2 NPs showed superb antibacterial activity against P. aeruginosa , E. coli , E. faecalis , Streptococcus sp., S. aureus and MRSA and were recommended as a dressing in the therapy of wounds [ 210 ]. Antibacterial effectiveness of CS/silicone rubber filled zeolite, Ag and Cu nanocomposites against P. aeruginosa and MRSA were reported by Rezazadeh and Kianvash [ 211 ]. A nanoscale hybrid consisting of CUR and CS layered on a hexagonal ZnO with average particle sizes of 48 nm showed greater antibacterial activity against MRSA and E. coli than antibiotic amoxicillin as well as anticancer activity with 24 h IC 50 value of 43.53 μg/mL using MCF-7 cell line [ 212 ].…”
Section: Applied Nanomaterialsmentioning
confidence: 84%
“…Nanocomposite films consisting of CS, and AgNPs, CuO NPs or TiO 2 NPs showed superb antibacterial activity against P. aeruginosa , E. coli , E. faecalis , Streptococcus sp., S. aureus and MRSA and were recommended as a dressing in the therapy of wounds [ 210 ]. Antibacterial effectiveness of CS/silicone rubber filled zeolite, Ag and Cu nanocomposites against P. aeruginosa and MRSA were reported by Rezazadeh and Kianvash [ 211 ]. A nanoscale hybrid consisting of CUR and CS layered on a hexagonal ZnO with average particle sizes of 48 nm showed greater antibacterial activity against MRSA and E. coli than antibiotic amoxicillin as well as anticancer activity with 24 h IC 50 value of 43.53 μg/mL using MCF-7 cell line [ 212 ].…”
Section: Applied Nanomaterialsmentioning
confidence: 84%
“…Previous studies showed that the interaction of Mtt and Cu or Ag NPs could cause an increase in their surface charge, increasing the adsorption capacity on bacteria, especially those with a negative charge in their cell wall, such as E. coli, , due to a decreased electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 99%
“…61 In the first 12 h, the necessary concentration that prevented the growth of both strains was 25 mg•L −1 Mtt_Cu/Ag, a concentration that was maintained until 24 h only for E. coli (Figure 7e,f and Table 2). Previous studies showed that the interaction of Mtt and Cu or Ag NPs could cause an increase in their surface charge, increasing the adsorption capacity on bacteria, especially those with a negative charge in their cell wall, such as E. coli, 62,63 due to a decreased electrostatic repulsion.…”
Section: Release Of Copper and Silver Ions Frommentioning
confidence: 99%
“…It has been used to enhance the photocatalytic activity of some wide-band gap semiconductors 12 . Silver and copper are among the most important toxic elements for gram positive and negative bacteria 13 , 14 . Furthermore, Ag nanoparticles in Na + -Y-zeolite and Cu 2+ nanoparticles in X-zeolite have excellent antibacterial activity 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Some adsorbents have low adsorption capabilities and can only be used under certain circumstances for the removal of dyes 30 . Also, the existence of antibiotic resistant bacteria is one of the biggest challenges to universal health because of their growing resistance to various antimicrobial substances 13 . Besides that, several components can be added with particular advantages to improve the dye removal and antibacterial performance of a single component.…”
Section: Introductionmentioning
confidence: 99%